IMPACT OF CLIMATE CHANGE ON TERTIARY EDUCATION IN NIGERIA - Adebayo, Adeniyi Daniels (Multi-Disciplinary Research and Development Journals Int’l, 2025)
This chapter examines how climate change affects tertiary education in Nigeria and proposes institutional strategies for adaptation and mitigation. Tertiary institutions—universities, polytechnics, colleges of education and vocational institutes—perform teaching, research and community service roles critical to national development. Nigeria faces substantial climate risks: model projections under high-emission pathways indicate large regional temperature increases through the twenty-first century, the country is assessed as highly vulnerable and relatively low in readiness for adaptation, and recent extreme events (notably the 2022 floods) caused large loss of life, displacement and damage to infrastructure and farmland. These risks damage campus infrastructure, disrupt academic calendars, constrain research (especially fieldwork), exacerbate food and water insecurity among students and staff, and widen educational inequality. The chapter synthesizes evidence and proposes practical, actionable strategies for tertiary institutions: institutional climate risk assessments, climate-proof infrastructure (drainage, passive cooling, solar power), green campus and biodiversity actions, curricular integration of climate education, emergency preparedness, partnerships for technical and financial support, and student-led resilience initiatives. Implementing these measures will protect educational continuity and position universities as hubs for climate adaptation research and community outreach.